Law Versus Humanity: Problems of the Non Refoulement Principle Regarding Refugees in Southeast Asia: Hukum Versus Kemanusiaan: Problematik Prinsip Non Refoulement Terkait Pengungsi di Asia Tenggara - Bakker, Felix Ferdin; Putri, Respati Triana; Chairunnisa, Dhea (Rechtsidee, 2022)
Legal issues related to refugees in Southeast Asia are influenced by the lack of regulations related to refugees in countries in Southeast Asia. This is related to the increasing number of refugees in Southeast Asia who are accepted by a country only based on humanitarian reasons. This study aims to examine the legal aspects related to the problem of refugees with the principle of non-refoulement related to refugees in Southeast Asia. This research is a normative legal research with a conceptual approach and legislation. The results of the study confirm that one of the legal aspects related to refugees in Southeast Asia is to strengthen regulations in each country in Southeast Asia. This includes also confirming the existence of the principle of non-refoulement by ratifying and becoming a party to the 1951 Convention and 1967 Protocol as an effort to provide legal certainty in implementing legal policies related to refugees. In addition, the role of the ASEAN Intergovernmental Commission on Human Rights (AICHR) plays an important role in providing welfare and protection for refugees from violence and discrimination. This is mainly by optimizing the involvement of ASEAN countries in providing direct assistance with the distribution of food, clothing and a decent living regardless of matters relating to citizenship. This is intended so that ASEAN countries' acceptance of refugees for humanitarian reasons is also limited and guided by legal products that guarantee legal certainty as well as the implementation of the principle of non-refoulement.